2018
DOI: 10.1029/2018gb005927
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonality of Physically Driven Export at Submesoscales in the Northeast Atlantic Ocean

Abstract: Submesoscale dynamics scriptO(1–100 km) are associated with enhanced vertical velocities and evolve on a time scale similar to that of biological production (hours to days). Here we consider an annual cycle of submesoscale dynamics and their relation to productivity and export in a small (20 × 20 km) region of the northeast Atlantic Ocean. In this region, a springtime bloom is initiated by restratification of the mixed layer in June, although intermittent shoaling of the mixed layer maintains phytoplankton po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 79 publications
7
60
0
Order By: Relevance
“…The idealized double gyre physical model used in this study resolves mesoscale eddies but does not fully resolve submesoscale dynamics, which would require a much higher horizontal resolution (McWilliams, ). It is therefore likely that the model underestimates vertical velocities and asymmetries in upward and downward transport (Gula et al, ; Mahadevan, ) and the strength of submesoscale instabilities (Erickson & Thompson, ). In addition, the model does not include high‐frequency winds and could therefore underestimate the downward mixing and export of DOC and POC along frontal structures (Whitt et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idealized double gyre physical model used in this study resolves mesoscale eddies but does not fully resolve submesoscale dynamics, which would require a much higher horizontal resolution (McWilliams, ). It is therefore likely that the model underestimates vertical velocities and asymmetries in upward and downward transport (Gula et al, ; Mahadevan, ) and the strength of submesoscale instabilities (Erickson & Thompson, ). In addition, the model does not include high‐frequency winds and could therefore underestimate the downward mixing and export of DOC and POC along frontal structures (Whitt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Here we will use the generic term ”eddy‐driven” vertical velocity, to refer to the range of (sub)‐mesoscale dynamics, that is, in the scale range 1–100 km. This eddy pump of POC could account for 20% to 70% of the local organic carbon export at the base of the euphotic layer (Llort et al, ; Omand et al, ; Stukel, Aluwihare, et al, Stukel, Song, et al ; Stukel & Ducklow, ) and has been identified as a potential pathway to transfer carbon to depths below the reach of the seasonal mixed layer (Erickson & Thompson, ). Nevertheless, previous observational and fine‐scale model estimates of the eddy pump were limited in space and time (typically a few eddy structures over a few weeks/months and the upper 100 m) and excluded the eddy effects on the subduction of DOC.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the first in situ estimates of phytoplankton carbon biomass seasonality in the open Southern Ocean observed by the BGC Argo floats deployed by the SOCCOM and SOCLIM projects. While limited in spatial coverage relative to satellites, these autonomous platforms provide year‐round profiles of optical backscatter in the top 2,000 m, allowing us to provide an estimate independent of chlorophyll, which is known to vary depending on the species and physiological state of phytoplankton (Behrenfeld & Boss, ; Cullen, ; Erickson & Thompson, ; Geider, ; Geider et al, ; Haëntjens et al, ) and to explore the three‐dimensional structure of phytoplankton dynamics. Our results suggest that using surface chlorophyll concentrations to detect the apex of the spring bloom can result in timing estimates that are delayed ∼1 month compared to when the vertically integrated biomass actually reaches its seasonal maximum and vice versa when using the proxy bulk biomass ( Cnormalpsurf×hML) particularly north of the SAF (Figures a–d and f).…”
Section: Discussionmentioning
confidence: 99%
“…Dall'Olmo and Mork () observed deep fluxes of small‐particle POC with Bio‐Argo floats in the Norwegian Sea and suggested that these were partly driven by the seasonal mixed‐layer pump. Likewise, Erickson and Thompson () showed that submesoscale instabilities of the mixed layer are a potential driver of export of fixed carbon, especially over a short time window in spring. Another alternative pathway was established by Omand et al (), who showed that eddy‐driven subduction can sustain a downward carbon flux accounting for as much as 25% of the total (sinking) export flux, likely exporting small size classes of POC and dissolved organic carbon.…”
Section: Introductionmentioning
confidence: 99%